Sexual Textualities Essays on Queer/ing Latin American Writing - Foster, David William (University of Texas Press, 2021)
Since the 1991 publication of his groundbreaking book Gay and Lesbian Themes in Latin American Writing, David William Foster has proposed a series of theoretical and critical principles for the analysis of Latin American culture from the perspectives of the queer. This book continues that project with a queer reading of literary and cultural aspects of Latin American texts. Moving beyond its predecessor, which provided an initial inventory of Latin American gay and lesbian writing, Sexual Textualities analyzes questions of gender representation in Latin American cultural productions to establish the interrelationships, tensions, and irresolvable conflicts between heterosexism and homoeroticism. The topics that Foster addresses include Eva Peron as a cultural/sexual icon, feminine pornography, Luis Humberto Hermosillo's classic gay film Doña Herlinda y su hijo, homoerotic writing and Chicano authors, Matias Montes Huidobro's Exilio and the representation of gay identity, representation of the body in Alejandra Pizarnik's poetry, and the crisis of masculinity in Argentine fiction from 1940 to 1960